2020
DOI: 10.3389/fnbeh.2020.00149
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Impairment of Fear Conditioning and Associated Brain Regions After Pilocarpine-Induced Status Epilepticus

Abstract: Our study aimed to demonstrate time-dependent declarative memory changes and its associated brain regions after status epilepticus (SE) using structural imaging techniques and machine learning methods. Pilocarpine was administrated to establish the SE model. At four different time points after SE (1, 2, 3, and 4 months, respectively), rats were subjected to structural imaging acquisition as well as contextual fear conditioning for the measurement of brain structural changes and declarative memory. Voxelbased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Similarly, Zubareva et al ( 54 ) showed a contextual memory decline (decreased freezing time in the familiar cage compared to the controls) in pilocarpine rats 60–70 and 70–90 days after SE ( 55 ). Interestingly, Qiu et al ( 56 ) found that pilocarpine rats had most severely impaired fear declarative memory at 2 months after SE, but then improved at 4 months while still performing worse than controls in CFC cues. However, one study reported an opposite result, i.e., an increased level of freezing response due to the auditory cue in delay protocol.…”
Section: Contextual Memorymentioning
confidence: 99%
“…Similarly, Zubareva et al ( 54 ) showed a contextual memory decline (decreased freezing time in the familiar cage compared to the controls) in pilocarpine rats 60–70 and 70–90 days after SE ( 55 ). Interestingly, Qiu et al ( 56 ) found that pilocarpine rats had most severely impaired fear declarative memory at 2 months after SE, but then improved at 4 months while still performing worse than controls in CFC cues. However, one study reported an opposite result, i.e., an increased level of freezing response due to the auditory cue in delay protocol.…”
Section: Contextual Memorymentioning
confidence: 99%